Are there Geographical Disparities in Access to Liver Transplantation in Atlantic Canada?. (2012) - Renfrew, Paul Douglas; Molinari, Michele
Abstract : OBJECTIVE: To characterize the patient population served by Atlantic Canada's Multi-Organ Transplant Program liver transplant service over the first five years of activity in its current iteration. METHODS: Data from a prospective institutional database, supplemented by retrospective medical record review, were used to identify and characterize the cohort of patients assessed for consideration of first liver transplant between December 1, 2004 and December 1, 2009. RESULTS: In the five-year period after reactivation, the program assessed 337 patients for first liver transplant. The median age at referral for this group of 199 men (59.0%) and 138 women (41.0%) was 56.1 years (range 16.3 to 72.3 years). The leading three liver diseases indicating liver replacement were alcohol-related end-stage liver disease (20.5%), hepatocellular cancer (16.6%) and hepatitis C-related end-stage liver disease (14.0%). When evaluated according to provincial population-standardized incidence, significant differences in the incidence of liver transplant assessment among the four Atlantic Canadian provinces were found (per 100, 000 inhabitants: Nova Scotia 19.8, New Brunswick 13.0, Newfoundland and Labrador 9.1 and Prince Edward Island 11.0; Fisher's exact P<0.001). Of the 337 individuals who began the assessment process, 153 (45.4%) were assigned to the wait list. The probability of an individual being assigned to the wait list was not found to differ according to province of residence (Nova Scotia 45.3%, New Brunswick 40.0%, Newfoundland and Labrador 58.7% and Prince Edward Island 40.0%; Fisher's exact P=0.206). CONCLUSIONS: The analysis suggests that there are geographical disparities in access to liver transplantation in Atlantic Canada. These disparities appear to be related to factors that precede the transplant assessment process.